2019
DOI: 10.1002/jclp.22745
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral functions underlying NSSI and eating disorder behaviors

Abstract: Objective This study examined whether the psychological functions motivating eating disorder (ED) and nonsuicidal self‐injury (NSSI) behaviors are similar, thereby representing shared mechanisms accounting for their high co‐occurrence. Method Self‐report data assessing NSSI, ED symptoms, and behavioral functions were collected from 676 adults with recent NSSI (past 6 months; n = 333) or disordered eating ( n = 343). Results Measurement invariance analyses revealed the same function‐factor structure for ED and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 49 publications
(62 reference statements)
2
13
0
Order By: Relevance
“…Factors potentially involved include body dissatisfaction and low self‐esteem (Perez et al, ). Growing evidence suggests that the risk of self‐harm is related to emotional dysregulation present in both EDs and patients who self‐harm or attempt suicide, where both self‐harm and altered eating behavior are used to self‐punish and avoid negative emotions (Muehlenkamp, Peat, Claes, & Smits, ; Muehlenkamp, Takakuni, Brausch, & Peyerl, ; Smithuis et al, ; Svirko & Hawton, ). Both groups of patients reported similar intent to hurt themselves both in the short and long term.…”
Section: Discussionmentioning
confidence: 99%
“…Factors potentially involved include body dissatisfaction and low self‐esteem (Perez et al, ). Growing evidence suggests that the risk of self‐harm is related to emotional dysregulation present in both EDs and patients who self‐harm or attempt suicide, where both self‐harm and altered eating behavior are used to self‐punish and avoid negative emotions (Muehlenkamp, Peat, Claes, & Smits, ; Muehlenkamp, Takakuni, Brausch, & Peyerl, ; Smithuis et al, ; Svirko & Hawton, ). Both groups of patients reported similar intent to hurt themselves both in the short and long term.…”
Section: Discussionmentioning
confidence: 99%
“…In sum, there is some evidence of functional equivalence between ED and NSSI. Findings revealed that similar intrapersonal such as affect regulation, and interpersonal functions such as interpersonal boundaries and autonomy, may be involved in the development and maintenance of both NSSI and ED behaviors (Muehlenkamp et al, 2019) and previous models of NSSI and ED behaviors highlight the role of similar emotion regulation de cits (e.g., Muehlenkamp et al, 2012).…”
Section: Emotion Regulation Nssi and Edmentioning
confidence: 67%
“…These negative and positive reinforcement patterns are consistent with neurobiological models of shared mechanisms across eating and substance use, functional assessment of binge eating/purging, and recent work in samples with comorbid binge eating and non-suicidal selfinjury. 13,37,38,64,65 This study has several strengths, including its large sample size and the use of semi-structured interviews reliably administered by trained doctoral research clinicians to assess clinically-significant impulsive behaviors and psychopathology. Further, because the DIPD-IV investigates impulsivity across many domains (eg, substance use, risky sexual behavior, and antisocial behavior), our categorization of general impulsivity included clinically-significant impulsive behaviors across a wider scope than prior work in "multiimpulsive" BN that was primarily defined based on self-harm and/or comorbid substance use.…”
Section: Discussionmentioning
confidence: 99%